THE RELATIONSHIP BETWEEN PSYCHOANALYSIS AND LITERATURE - Musayeva Dilsuz Tuychiyevna, (EPRA International Journal of Research and Development (IJRD), 2023)
Austrian physician and scientist Sigmund Freud’s psychoanalytic concept, which emerged at the beginning of the XX century, greatly influenced the spiritual culture of the 20th century. Z. Freud’s philosophical ideas based on the results obtained in the field of neurosis therapy and the study of the mental processes of the unconscious, as well as their openness to understanding and broad perspectives for explaining the mechanisms of social life, human behavior, the nature of scientific and artistic creativity psychoanalysis gained great importance not only in the eyes of scientists but also in creative intellectuals and the general public. This paper highlights the emergence of psychoanalysis as a field of science and its close relationship with literature by analyzing the works of well-known psychologist Sigmund Freud as well as his influence on the psychoanalytic approach to literature.